Knowledge Overview of Thirdtrimester Pregnant Women and Women in Labor about the Rebozo Technique - Astuti, Agnes Dwiana Widi; Intanwati, Intanwati; Presty, Marsela Renasari; Yasinta, Animora (GLOBAL HEALTH SCIENCE GROUP, 2024)
One of the efforts that can be made to reduce pain, prolonged labor (congestion) and prepare the mother for childbirth is through the rebozo technique. The rebozo technique is a non-pharmacological method without the use of drugs to help reduce pain during labor. Objective: To determine the knowledge of third-trimester pregnant women and women giving birth regarding the Rebozo technique. Method: The method used in this research is descriptive method. The researcher's research sampling technique used a total sampling technique. This research was conducted on 12 – 19 May 2023, the sample size was 35 people. The research instrument used a questionnaire. Results: This research used univariate analysis using frequency distribution to provide an overview of the respondents characteristics. Respondents knowledge about the definition of rebozo was 26 (74.3%) respondents had poor knowledge, 29 (82.9%) respondents had moderate knowledge about the benefits of rebozo, 30 (85.7%) respondents had poor knowledge about the rebozo technique, and 29 respondents had poor knowledge about rebozo contraindications ( 82.9%) respondents had moderate knowledge. Then regarding respondents' general knowledge regarding rebozo, 28 (80%) respondents had poor knowledge. Conclusions: Description of the knowledge of third-trimester pregnant women and women giving birth regarding the Rebozo technique at PMB Utin Mulia Pontianak in 2023. Based on the result, it can be concluded that the majority of respondents, namely 28 (80%) respondents, have poor knowledge. The existence of research on rebozo can be used as evaluation material and input for every health care provider as well as further increasing information and learning about rebozo in hospitals, health centers or in private or private clinics.